Body dismorphic disorder - Korabiusz, Katarzyna; Wawryków, Agata; Fabian-Danielewska, Anna; Stecko, Monika; Wilczyńska, Agnieszka; Janik-Fuks, Inga; Maciejewska, Martyna (Journal of Education, Health and Sport, 2019)
Dysmorphophobia (BDD), also called the obsession of perfection, is a disorder involving the extreme negative assessment of one’s own appearance resulting from a slight defect that is exaggerated. Dysmorfophobia belongs to hypochondriac disorders. This disease affects 0.7-2.4% of the total population, but knowledge about it is still not common. Perceptual disorders most often affect the skin, hair, nose, body weight, stomach, breasts, eyes, thighs and teeth. Legs, body build, face and face size are less often. In addition to typical psychotherapy, well-chosen relaxation techniques and cognitive-behavioral therapy as well as pharmacotherapy are also applied.